Word-finding difficulty is a prevalent disease-related deficit in early multiple sclerosis. (November 2020) - Brandstadter, Rachel; Fabian, Michelle; Leavitt, Victoria M; Krieger, Stephen; Yeshokumar, Anusha; Katz Sand, Ilana; Klineova, Sylvia; Riley, Claire S; Lewis, Christina; Pelle, Gabrielle; Lublin, Fred D; Miller, Aaron E; et al.
Background: Persons with multiple sclerosis (MS) commonly report word-finding difficulty clinically, yet this language deficit remains underexplored. Objective: To investigate the prevalence and nature of word-finding difficulty in persons with early MS on three levels: patient report, cognitive substrates, and neuroimaging. Methods: Two samples of early MS patients ( n = 185 and n = 55; ⩽5 years diagnosed) and healthy controls ( n = 50) reported frequency/severity of cognitive deficits and underwent objective assessment with tasks of rapid automatized naming (RAN), measuring lexical access speed, memory, word generation, and cognitive efficiency. High-resolution brain magnetic resonance imaging (MRI) derived measurements of regional cortical thickness, global and deep gray matter volume, and T2 lesion volume. Relationships among patient-reported word-finding difficulty, cognitive performance, and neural correlates were examined. Results: Word-finding difficulty was the most common cognitive complaint of MS patients and the only complaint reported more by patients than healthy controls. Only RAN performance discriminated MS patients with subjective word-finding deficits from those without subjective complaints and from healthy controls. Thinner left parietal cortical gray matter independently predicted impaired RAN performance, driven primarily by the left precuneus. Conclusion: Three levels of evidence (patient-report, objective behavior, regional gray matter) support word-finding difficulty as a prevalent, measurable, disease-related deficit in early MS linked to left parietal cortical thinning.